ANALISIS STRATEGI PEMASARAN MASKAPAI LION AIR PADA MASA PANDEMI COVID-19 DI BANDAR UDARA SULTAN HASANUDDIN MAKASSAR - Muh Dody Alfayed; Ika Fathin Resti Martanti (Pusat Riset dan Inovasi Nasional, 2023)
An airport is a land and water area with certain boundaries that is used as a place for aircraft to land and take off, boarding and dropping passengers, loading and unloading goods, and places for intra and inter-mode transportation, which are equipped with aviation safety and security facilities, as well as other facilities. products and other supporting facilities. Lion Air is the largest private airline in Indonesia, where the airline controls most of the domestic market share. This study used qualitative research methods. Qualitative research methods are often called naturalistic research methods because the research is carried out in natural conditions (natural settings). The results of this study explain the marketing strategy at the Air Lion Airline which, the challenges of implementing MPR include HR implementing Marketing Public Relations must be able to develop and improve IT capabilities on the basis of intellectual capacity, must understand data from research results, must understand the flow of research base data analysis , and coordination with related parties so that there is no coordination gap, must be able to have good relations with management who is the decision maker, HR implementing Marketing Public Relations must have a team leader mindset, and provide input to superiors.